2010
DOI: 10.1037/a0020651
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceived discrimination as a postadoption risk factor for internationally adopted children and adolescents.

Richard M. Lee

Abstract: Parental perceived discrimination was investigated as a risk factor in a U.S. sample of 1,579 internationally adopted children ages 5 to 18 years. Drawing on stress proliferation theory, we hypothesized a positive association between parental perceived discrimination and child problem behaviors, controlling for preadoption adversity. We also expected differences by world region and age of the child. Adoptive parents with Asian and Latin American children reported more discrimination than parents with Eastern E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 53 publications
(71 reference statements)
6
49
0
2
Order By: Relevance
“…Some authors suggest such a link, but do not assess it (Lee and MIAP 2010;Friedlander et al 2000). Of those who do, Basow et al (2008), DeBerry, Scarr, andWeinberg (1996) and Yoon (2000Yoon ( , 2004 observed a positive association between racial socialization and ethnic identity, and in turn psychological adjustment.…”
Section: Critical Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…Some authors suggest such a link, but do not assess it (Lee and MIAP 2010;Friedlander et al 2000). Of those who do, Basow et al (2008), DeBerry, Scarr, andWeinberg (1996) and Yoon (2000Yoon ( , 2004 observed a positive association between racial socialization and ethnic identity, and in turn psychological adjustment.…”
Section: Critical Reviewmentioning
confidence: 92%
“…Moreover, participants' age may have affected the results; identity concerns are usually associated with adolescence and young adulthood, while many authors conducted their studies with adoptees younger than ten years (e.g. Friedlander et al 2000;Lee and MIAP 2010;Huh and Reid 2000) and/or with a large sample age range (e.g. Lee and MIAP (2010) with participants aged five to eighteen years).…”
Section: Critical Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, social stigma continues to be identified as a significant challenge to members of marginalized social groups, and research does support its influence as a detriment to healthy psychological development in adopted persons (Lee, 2010). The social stigma surrounding adoption and the concept of birth privilege are viewed here as major components to underlying processes of self-esteem.…”
Section: Self-esteem and Birth Privilegementioning
confidence: 98%
“…As such, the pressure associated with birth privilege may produce lasting consequences for the formation of internalized attitudes toward one's own adoptive status, subsequent actions toward integration of adoption as a contingency of self-worth, and ultimately, the development of self-esteem as an adopted person. While connections between discrimination and poor psychological functioning have been proposed in adopted persons (Lee, 2010), implications of social forces on the formation of selfesteem remain largely unincorporated in mainstream adoption theory.…”
Section: Adopted Persons As Deficientmentioning
confidence: 99%